Overcoming the Limits of EMU Through Covid? Next Generation EU Against the Unaddressed Needs for Ambitious Structural Reform - Ceron, Matilde; Palermo, Carlo Maria (PARTECIPAZIONE E CONFLITTO, 2021)
The article considers the long-standing limits of the Economic and Monetary Union (EMU) through the lenses of Next Generation EU (NGEU) pandemic response evidencing how Covid-19 exacerbated EMU shortcomings are (not) overcome. We evaluate whether NGEU is only a palliative stop-gap fix to structural problems and how for Covid-19 to be considered as a breaking point for EU economic governance permanent ambitious (Treaty) reform is an essential and so far not uncontested step. A qualitative systematic review of weaknesses of EMU and proposed reforms informs a scoreboard evaluation of NGEU. Results confirm that while the symmetric crisis allowed suspending risk-sharing and solidarity vetoes, deep structural asymmetries and unfitness of (intergovernmental) decision-making cannot be addressed through NGEU temporary emergency mechanism. Hence Covid-19 so far cannot be narrated as sparking a revolutionary deviation from the architecture and guiding principle of the supranational fiscal framework. At the same time, the pandemic opened a (short-lived) window of opportunity for completing the EMU, requiring permanent structural institutional (Treaty) reform. A timely finding – grounded in copious extant literature on the EMU – highlighting the high stakes of the ongoing Conference of the future of Europe, whose success can only materialise through an ambitious (federal) agenda.